Upaya Meningkatkan Keaktifan Siswa Dalam Pembelajaran Ilmu Pengetahuan Sosial Terpadu Melalui Strategi Pembelajaran Index Card Match (Mencari Pasangan) Pada Siswa Kelas VIII E Sekolah Menengah Pertama Muhammadiyah 4 Surakarta Tahun Pajaran 2015/2016 - Pradista, Ariska Devie (2016)
The purpose of this study is to enhance the activity of students in the Integrated Social Science through learning strategies index card match (mencari pasangan) at class VIII E Junior High School Muhammadiyah 4 Surakarta. This type of research is a classroom action research (PTK) by using qualitative descriptive analysis is by analyzing the data the development of students of the first cycle to the second cycle. This classroom action research subject is class VIII E SMP Muhammadiyah Surakarta 4 the number of students 32 students. The subject of the implementation of the action is a researcher assisted by the Integrated Social Science teachers. Classroom action research using data collection methods such as observation, interviews, and documentation. The procedure in this study, there are four stages: planning, implementation, observation, and reflection. The data analysis technique used is critical for process analysis techniques and techniques for results comparison. The results showed an increase in activity of students in learning through learning strategies Integrated IPS index card match (mencari pasangan). It can be seen from: 1) the students' attention to the teacher's explanation, 2) liveliness ask, 3) the student's ability to express opinions, 4) gives a brilliant idea, 5) do the exercises. Prior to the implementation of the average cycle student activity by 36.25%. In the first cycle the average activity of students increased to 61.25%. In the second cycle the average activity of students increased to 88.75%. This means increased activity of students exceeds the indicators of success, namely 75%. Based on research data of the class action, it can be concluded that through the application of learning strategies index card match (looking for a partner) can increase student activity on Integrated Social Science subjects.